ANALISIS PENINGKATAN KUALITAS STATIONARY CONTACT MENGGUNAKAN METODE STATISTICAL PROCESS CONTROL DAN PROCESS FAILURE MODE AND EFFECT ANALYSIS PLATE PADA PERUSAHAAN METAL PLATING DAN STAMPING - Emilza, Alif Abdhil Hakim; Saryatmo, M. Agung; Sukania, I Wayan (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
The increasingly intense global competition demands that companies improve product quality in order to remain competitive in the market. At a metal plating and stamping company, a defect rate of 2.29% was identified, which exceeds the established standard by 0.29%. This study aims to identify the types of defects present in the company and their causes, with the goal of providing recommendations to improve production quality—specifically for the stationary contact plate product—using the Statistical Process Control (SPC) and Process Failure Mode and Effect Analysis (PFMEA) methods. Production and defect data were collected from January 2024 to March 2025 and implemented in April 2025 using checksheets, Laney P-charts, and Pareto diagrams to identify the types and frequency of defects. The results revealed three main types of defects: dented, bending, and scratch, with scratch being the most frequent. Further analysis using a fishbone diagram helped identify the root causes of the defects and prioritize corrective actions based on the Risk Priority Number (RPN). The proposed improvements include technical recommendations such as adding foam padding to the output container, reducing the distance between the stamping machine and the output container, and implementing a daily checksheet at the beginning of the production process.